The Rhetorical analysis of a documentary photograph - Rolf Gaede (Communicare)
This article consists of three sections. In the first section, the theoretical foundations of rhetorical analysis as applied to visual messages is explicated. In the second section, the approach is illustrated by means of an example drawn from a photographic essay on streetchildren. In the third section, some difficulties with the application of rhetorical analysis to documentary photographs are discussed. It is theorized that straight documentary photographs are essentially open texts and that even though the structural data uncovered in' the course a rhetorical reading might point towards a preferred interpretation, decisions about the author's persuasive intent with the image can only be made if the creative controls of the medium have been employed rhetorically.